Y-Function Analysis of the Low Temperature Behavior of Ultrathin Film FD SOI MOSFETs - A. Karsenty; A. Chelly (Active and Passive Electronic Components)
The respective transfer characteristics of the ultrathin body (UTB) and gate recessed channel (GRC) device, sharing same W/L ratio but having a channel thickness of 46 nm, and 2.2 nm respectively, were measured at 300 K and at 77 K. By decreasing the temperature we found that the electrical behaviors of these devices were radically opposite: if for UTB device, the conductivity was increased, the opposite effect was observed for GRC. The low field electron mobility and series resistance RSD values were extracted using a method based on Y-function for both the temperatures. If RSD low values were found for UTB, very high values (>1 MΩ) were extracted for GRC. Surprisingly, for the last device, the effective field mobility is found very low (<1 cm2/Vs) and is decreasing by lowering the temperature. After having discussed the limits of this analysis.This case study illustrates the advantage of the Y-analysis in discriminating a parameter of great relevance for nanoscale devices and gives a coherent interpretation of an anomalous electrical behavior.